(untitled) (Ustozlar uchun, 2025)
Methods of teaching in any subjects being important factor for people who work the spheres relating in educational system analyze in this research work. Gaining certain knowledge in the particular area is to be considered the grand notions in the process of teaching subjects. In different circumstances teachers should select and make use of appropriate approaches to achieve satisfactory results in variety of learning procedures. This study can be used in every sphere of institutional organizations. It identifies main features of methodology of conducting lessons through the certain mechanism of teaching and reveals the scientific characteristics of the processes within the lesson.